(untitled) (Pedagogy of Higher and Secondary Education, 2014)
Polishchuk N. V. Requirements for education and training spiritual teacher in the era of information and high-tech science and technology The articles deals with the issues concerning transforming educational system in conditions of an informational and highly technological society in which information, knowledge and technology represent themselves as the main social values. It is shown, that modernization of modern formation in a context of increase of efficiency of its influence on professional self-determination of the person in system of market and democratic transformations, and also in a context of growth of spirituality of youth is necessary.